CORTICOSTEROID-INDUCED CENTRAL SEROUS CHORIORETINOPATHY - Nursalim, Ade John; Sumual, Vera (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Central Serous Chorioretinopathy (CSC) is a condition where there is an accumulation of serous fluid in the retinal pigment epithelium layer. The abnormality in the retinal pigment layer of the eye causes vision loss and serous detachment. CSC has a variety of causes, one of which is corticosteroid therapy. This article aims to report a case of a 27-year-old male patient who was diagnosed with CSC. The risk factor indicating CSC, in this case, was long-term oral and the use of a nasal spray to treat patient?s allergic rhinitis. Patients have allergic rhinitis and sneezing. Thus, they are administered to consume tablets of 16 mg methylprednisolone three times a day. The patient has a history of using a nasal spray containing 0.05% mometasone furoate monohydrate for ten years in a row. The patient?s visual acuity is 6/6 on his right eye and 6/15 on his left eye. Posterior segment examination and optical coherence tomography (OCT) were considered effective in identifying the features of patients with CSC, and thus both were administered. It was further found that steroid therapy replacement and healthier lifestyle adjustments could sustain the symptoms and improve the patient?s well-being.